If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + p = 7(p + -10) Reorder the terms: 28 + p = 7(-10 + p) 28 + p = (-10 * 7 + p * 7) 28 + p = (-70 + 7p) Solving 28 + p = -70 + 7p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-7p' to each side of the equation. 28 + p + -7p = -70 + 7p + -7p Combine like terms: p + -7p = -6p 28 + -6p = -70 + 7p + -7p Combine like terms: 7p + -7p = 0 28 + -6p = -70 + 0 28 + -6p = -70 Add '-28' to each side of the equation. 28 + -28 + -6p = -70 + -28 Combine like terms: 28 + -28 = 0 0 + -6p = -70 + -28 -6p = -70 + -28 Combine like terms: -70 + -28 = -98 -6p = -98 Divide each side by '-6'. p = 16.33333333 Simplifying p = 16.33333333
| (3)k-5=18 | | (3)k-5=15 | | x=tanh(ax) | | 7=3a+5a+1a+7 | | 0=5m^2n^3-(6mn-4m^2n^3+3)+6 | | f(a)=2a^2-a+4 | | 0=4x^2+3x(-9x+6) | | 0=5(2-x)+3(5x-4) | | 39c-17=358 | | 5x+12x-41=5y | | 0=23+2ab+3c-(c+2ba) | | 0=23+2ab+3c-(c+2ab) | | 0=2ab+b^2-(3ab+1)-5 | | 0=3x-5y+1-(4x+y-3) | | .20x+20=.30x+12 | | 3x-7+-4x-8= | | 3x+7=-2x-18 | | 0=2x-3(x-xy)+6(x-2xy) | | 0=4z-(5-2z)-4 | | -x+10=2x+19 | | 0=4(x-2y)-3(2x-y) | | (4x-21)(x+3)= | | 0=3(2x+6)-(2x-y) | | 0=6a-(4-a)-3 | | -4k-18=-2+2(7k-8) | | 9y+3(5-y)= | | 9x+y=-9x | | 35=19m-m+5 | | 10y+x=-28 | | 13y-8y-12=58.75 | | 10x+y=28 | | 7x^2+26x=-8 |